Penegakan Hukum Tindak Pidana Kecelakaan Lalu Lintas Yang Mengakibatkan Kematian - Akbar Panggabean, Windro; Triwiraputra, Ega Laksmana; Sudarmanto, Kukuh; Arifin, Zaenal (Universitas Semarang, 2024)
This study aims to analyze the performance of Police Sector intelligence as a detection base in supporting the maintenance of security and public order and analyze the efforts to improve the performance of Police Intelligence as a detection base in supporting the maintenance of security and public order in the Batang Police Department. The research method used is a sociological juridical. The analysis of research results shows that early detection efforts carried out by the Sector Police Unit of the Batang Resort Police security intelligence unit really need to be carried out so that they are able to detect, search and collect and dig up information from the community, then an identification process is carried out to sort, calculate and determine alternatives and consider and reading the signs of the facts from the detection results, the results are expressed in intelligence administration in the form of products that guarantee confidentiality, speed, accuracy and predictability. The discipline of the Batang Police Sector personnel in understanding the regulations and policies of leaders who are obliged to work is still lacking, as evidenced by the finding that the implementation of the Sector Police as a Detection Base has not run optimally, both operationally in the field and administratively.